2017
DOI: 10.2147/dmso.s130834
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor agonists: a systematic review of comparative effectiveness research

Abstract: BackgroundGlucagon-like peptide-1 receptor agonists (GLP-1RAs) act by increasing insulin secretion, decreasing glucagon secretion, slowing gastric emptying, and increasing satiety.ObjectivePublished evidence directly comparing GLP-1RAs with other approved treatments for type 2 diabetes (T2D) was systematically reviewed.MethodsA literature search was performed using MEDLINE and Embase databases to identify papers comparing GLP-1RAs with other classes of glucose-lowering therapy in patients with T2D.ResultsOf th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 78 publications
(195 reference statements)
3
80
0
7
Order By: Relevance
“…Our analyses, however, are the most updated and robust including 13 RCTs with total of 4330 participants evaluated. Notably, other systematic reviews and meta‐analyses have compared GLP‐1 agonists with DPP‐4 inhibitors but their reports do not undercut the novelty of our current meta‐analyses . Specifically, Levin et al reported a systematic review of studies comparing GLP‐1 agonists with DPP‐4 inhibitor but did not include meta‐analyses of these data.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Our analyses, however, are the most updated and robust including 13 RCTs with total of 4330 participants evaluated. Notably, other systematic reviews and meta‐analyses have compared GLP‐1 agonists with DPP‐4 inhibitors but their reports do not undercut the novelty of our current meta‐analyses . Specifically, Levin et al reported a systematic review of studies comparing GLP‐1 agonists with DPP‐4 inhibitor but did not include meta‐analyses of these data.…”
Section: Resultsmentioning
confidence: 95%
“…Notably, other systematic reviews and meta-analyses have compared GLP-1 agonists with DPP-4 inhibitors but their reports do not undercut the novelty of our current meta-analyses 31,32. Specifically, Levin et al31 reported a systematic review of studies comparing GLP-1 agonists with DPP-4 inhibitor but did not include meta-analyses of these data. Moreover, in the study of Pinelli et al, 32 the research question differed from our analyses insofar as only long-acting GLP-1's agonists were compared to DPP-4 inhibitors.…”
mentioning
confidence: 92%
“…Certainly, relative to sulfonylurea (SU) or insulin, the lower risk of hypoglycaemia with AHA is clear and widely accepted . However, relative to placebo, efficacy‐focused studies have been unable to delineate hypoglycaemia risk with these newer AHA, mainly due to the use of background SU and insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Safety of different antihyperglycaemic agents at different stages of eGFR receptor agonists then, work by the stimulation of GLP-1 receptors, enhancing insulin secretion, appetite suppression, delaying gastric emptying, and inhibiting glucagon release from the pancreas 55. Current clinically used GLP-1 RAs are resistant to Dipeptidyl Peptidase 4 (DPP4) cleavage and are generally long-acting drugs, reducing HbA1C with a variability between 1.3% and 1.9% 56. GLP-1-RAs use has increased in the past decade due to their efficacy and mostly due the low risk for hypoglycaemia and their beneficial effect on weight loss 57.…”
mentioning
confidence: 99%